Hidden Facts and The Representation of Indonesia within Mamiya Mosuke’s “Kichi no Seikatsu” - Dewi Anggraeni (Universitas Diponegoro, 2021)
Despite witnessing modernization in Indonesia, nanpōchōyōsakka (South-dispatched writers) depicted Indonesians as people who remain undeveloped because of Western colonialism. This article argues that there must be “hidden facts” behind the representation of Indonesia within the writers’ works due to a mission of disseminating the idea of the Greater East Asia Co-prosperity Sphere. Using Mamiya Mosuke’s military essay “Kichi no Seikatsu” as the object of study, this article seeks to explain what kind of “Indonesia” Mamiya represents and the impact of such representation on “Indonesia” as a spatial concept by illuminating “hidden facts” behind his expressions. This article employs the concept of contact zone (Mary Louise Pratt) to view Indonesia as a social space already shaped by Dutch colonialism and uses sakuhinron method to analyze Mamiya’s expressions in representing Indonesia. Through analysis, Mamiya portrays Indonesians as reliant people and blames such conditions on the Dutch colonial policy while leaving local intellectuals and nationalist movements out of his narrative. This article concludes that Mamiya justifies the notion of the Greater East Asia Co-prosperity Sphere by denying Indonesian agency, gives an impression that Indonesians need Japanese guidance to stand on their own. Keywords: Contact Zone; Kichi no Seikatsu; Mamiya Mosuke; Nanpōchōyōsakka; Representation